Flow cytometric analysis of DNA synthetic phase fraction of the normal appearing colonic mucosa in patients with colorectal neoplasms. Issue 3 (September 1995) - Nakamura, S; Goto, J; Kitayama, Y; Sheffield, J P; Talbot, I C
Abstract : DNA synthetic (S) phase fractions of normal appearing colonic mucosa in Japanese and British patients with colorectal neoplasms were compared with those in patients without colonic neoplasms. Normal crypts were isolated from fresh surgical specimens of the large intestine by the use of EDTA. After fixation with 70% ethanol, isolated crypts were digested with pepsin into single nuclei suspensions. These were stained with propidium iodide and examined by flow cytometry. S phase fraction was calculated from the flow cytometry DNA histogram using Baisch's method. S phase fractions of normal appearing crypts in Japanese and British patients with colorectal tumours were not significantly different and analysed together. S phase fraction of normal appearing colonic crypts in 14 patients with familial adenomatous polyposis (FAP) was 10.23 (2.59%) (mean SD)) ranging from 5.8 to 18.8. S phase fraction of background normal mucosal in patients with large adenomas (over 2 cm) and adenocarcinomas were 9.74 (3.76%) (range, 2.7-16.1) and 8.93 (3.54%) (range, 2.9-18.9) respectively. In normal mucosa of patients without any colorectal neoplasms, S phase fraction was 8.99 (3.94)% (range, 3.9-17.7). There was no statistically significant difference in S phase fractions of normal mucosa in the four groups. Our results show that an increase in proliferative activity of background colonic crypts is not necessary for tumour development.